1995
DOI: 10.3354/dao022101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen deficiency on the disease status of common dab Limanda limanda

Abstract: ABSTRACT-An epidemiological survey of the fish diseases lymphocystis, epidermal papilloma and skin ulcers in common d a b Limanda limanda L. was conducted in the southern Kattegat each year in May from 1984 to 1993. During the period of investigation, severe oxygen depletion occurred in late summer 1986 and 1988. After the oxygen deficiency in 1986. the occurrence of lymphocystis and epidermal papilloma increased and peaked in 1989 with prevalences of 14 7 and 3.3%, respectively. The prevalence of skin ulcers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 11 publications
5
40
0
Order By: Relevance
“…The highest prevalences for lymphocystis and epidermal papilloma were observed in Area 1 (German Bight) and in Area 2 (off the west coast of Denmark) and for skin ulcers in Area 4 (Skagerrak). Similar temporal parallelisms between the diseases lymphocystis and epidermal papilloma have been described before from the German Eight and the Dogger Bank (Dethlefsen 1990) and from the Kattegat (Mellergaard & Nielsen 1995), where statistically significant correlation was found between the 2 diseases. In the present study, these diseases were also found positively correlated in the Areas 1, 2 and 3 but this correlation was not statistically significant.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…The highest prevalences for lymphocystis and epidermal papilloma were observed in Area 1 (German Bight) and in Area 2 (off the west coast of Denmark) and for skin ulcers in Area 4 (Skagerrak). Similar temporal parallelisms between the diseases lymphocystis and epidermal papilloma have been described before from the German Eight and the Dogger Bank (Dethlefsen 1990) and from the Kattegat (Mellergaard & Nielsen 1995), where statistically significant correlation was found between the 2 diseases. In the present study, these diseases were also found positively correlated in the Areas 1, 2 and 3 but this correlation was not statistically significant.…”
Section: Discussionsupporting
confidence: 55%
“…Dethlefsen (1990) found that low oxygen levels may be one of the stress factors contributing to the outbreak of lyrnphocystis and epidermal papilloma in the German Bight. It has not been possible to establish significant correlations between lymphocystis and epidermal papilloma and oxygen deficiency in the present material as were demonstrated for the Kattegat (Mellergaard & Nielsen 1995), probably due to the lack of baseline prevalence data for the areas (i.e. before the oxygen deficiency occurred).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations